THE EFFECTIVENESS OF OMEGA-3 MACKEREL FISH OIL ON THE DENSITY OF TOOTH ENAMEL In Vivo Study of White Rat (Rattus novergicus) - Sandy Christiono; Arina Manashika; Erdianto Setya Wardhana (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Consuming cariogenic foods can cause calcium demineralization which is characterized by the appearance of dental caries. One effort on the prevention of dental caries is by consuming Mackerel fish oil that contains omega-3 fatty acids, omega-6 fatty acids, and vitamins that are beneficial for the body. Purpose: The study aimed to determine the effectiveness of omega-3 Mackerel fish oil on the density of tooth enamel in white rat (Rattus norvegicus). Method: This study applied an experimental research method with randomized posttest only control group design. Samples were comprised of 20 rats taken from 6 pregnant female rats which later divided into two groups: a treatment group administered orally with omega-3 Mackerel oil as much as 1ml / 200 mg BB and an aquadest control group. The treatment was administered during pregnancy period until the eruption of the teeth. Rats were euthanized to extract the tooth and enamel density was observed using micro-CT. The data were then analyzed with Levene’s homogeneity test and were preceded to independent T-test. Result: The average enamel density of the treatment group was 1155.18340 while the control group was 175.91640. Based on independent t test between the two groups, a significant difference in tooth enamel density of Rattus Noevegicus was obtained (p <0.05). Conclusion: The administration of omega-3 Mackerel fish oil may increase the density of tooth enamel in White Rat (Rattus norvegicus).